Práticas pedagógicas inovadoras em Educação Física: o estudo de um caso - Almeida Callai, Ana Nathalia (2024)
This article seeks to characterize the performance of a Physical Education teacher who implements innovative practices in school. Using a qualitative approach, a case study was conducted, collecting data through a semi-structured interview, observations of 20 classes transcribed in a field diary, and normative documents from both the university where the teacher received initial training and the school where he works as a teacher. Data were analyzed through thematic content categorization. The elements characterizing the teacher's actions as innovative practices include formative engagement beyond the mandatory hours, the continuous pursuit of in-service training to enhance the quality of their teaching, coherence between their pedagogical discourse actions, and an evaluation process that actively involves students in the construction of knowledge. Their innovative actions are marked by moments of dialogue, listening, and problematization, focusing their classes on the community's realities while integrating universal aspects of scientific knowledge. Furthermore, he maintains fidelity to the specific curricular contents of Physical Education to broaden the student's knowledge and experiences critically.